UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MEMANFAATKAN PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR DENGAN MENERAPKAN METODE DISKUSI KKG DI SDN GERIH 1 KECAMATAN GERIH KABUPATEN NGAWI TAHUN 2018-2019 - Purnami Purnami (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2022)
The purpose of this research is to improve teachers' ability to use the school library as a learning resource through discussions in the Teacher Working Group (KKG) at SDN GERIH 1. Teachers can perfect the learning methods applied in schools so as to increase creativity, motivation and student learning outcomes. This research was designed in the form of School Action Research which was planned to be carried out in two cycles, where each cycle was carried out in two to three meetings. The subjects of this study were teachers at SD Negeri GERIH 1 consisting of 9 class teachers.In the first cycle the average value obtained from the attitude of the teacher discussing the discussion was 78.89 in the